Does Inclusion in the Sustainability Index Contribute to the Financial Performance of the Companies: Evidence from Developing Countries - Füsun Küçükbay; Begüm Güler (Journal of Economy Culture and Society)
This study investigates whether the performance of the companies is affected when they are included in the Sustainability Index. The study deals with companies operating in Brazil and Turkiye, in this respect, the panel data analysis technique is applied. ROA (Return On Assets) is used for the dependent variable, while independent variables are debt/equity ratio, company size, operational ratio and the Sustainability Index. The results of the study reveal that taking part in the Sustainability Index has a statistically significant positive effect on profitability for both Brazil and Turkiye. When the other results are analyzed, it is seen that there is a negative relationship between the debt / equity ratio and ROA for the case of Turkiye